Augmented Reality Research Trends in Indonesia: A systematic Literature Review - M. R. Firmantara; I. Mudakir; N. Nuriman (Universitas Negeri Yogyakarta, 2023)
Augmented Reality (AR) may be defined as a technology capable of incorporating two-dimensional or three-dimensional virtual objects into a real environment. This content analysis study aimed to systematically analyze AR research trends in Indonesia based on articles published in national and international journals. It compared the two methods in applying AR, namely Marker Based 77% and Markerless Based 23%. No output appeared in 2013, 2014, and 2016, while 2022 had the highest productivity with 12 papers. A significant increase in the number of articles was seen from 2018 to 2022, where 2021 and 2022 were the most productive year with 40 publications, and 639 was the highest number of citations in 2022. The AR research method dominated by research and development (40%), followed by a literature review (23%), experiment (13%), mixed method (8%), survey (4%), classroom action research (4%), and correlational (3%). Furthermore, the number of articles with 2 authors experienced a rapid increase between 2020 and 2022 and more than half of publications (66%) were written by the collaborations of 2 authors and 3 authors.